(untitled) (Actual Problems of Mind, 2024)
Human capital can be considered a fundamental characteristic of a developed society, as it becomes a prerequisite for the public good in its form of intellectual abilities and practical skills while determining human capacity for self-realization and high-quality work. Human capital grows through investments, and education is considered one of them. However, focusing solely on the instrumental or economic aspect of human capital is not comprehensive; economic and value aspects can be seen as complementary. If profitability emerges as a form that realizes not only professional skills but also a value system or type of “intelligence”, the question arises: is modern education of sufficient quality to be not only economically justified but also socially efficient? What specific forms of intellectual activity might be used in the process of training modern leaders? The authors of the article claim that the 21st century is witnessing an “aesthetic renaissance”, as a result of which aesthetic values are regarded as those that enable added value, influencing informational and economic contexts, among others. Aesthetic excellence is becoming an increasingly important factor. At the same time, in the modern theory of teacher training, the aesthetic foundation of leadership potential remains insufficiently appreciated. The deficit of philosophical thinking among leaders, and the narrowing of emotional, ethical, and aesthetic intelligence, remains a real practical issue that requires additional attention. The article explores the prospects of the modern leadership paradigm focused on value-philosophical and aesthetic models of forming and functioning emotional intelligence as the foundation of human capital, considering the systemic changes occurring in the educational sphere. The key theme of the study is aesthetic intelligence as a topical educational value, its role, essence, advantages, characteristics, morality, and aestheticism—a purposeful clarity of thought that, under favourable circumstances, ensures successful outcomes. The analysis of modern approaches in leadership theory demonstrates the research focus on the creative foundations of leadership intellectual culture, which do not contradict contemporary views on the multidimensionality of intelligence and rationality. None of the types of intelligence can be considered dominant. Modern intellectual criteria extend beyond the rational standard: they interpret reason as a creative phenomenon, consider multiple ways of perceiving the world and interacting with it, and incorporate the aesthetic criterion into the epistemological framework. Therefore, it is reasonable to justify the view that aesthetics, art, and science can be understood as forms of knowledge and products of aesthetic intelligence. Aesthetic intelligence manifests in aesthetic taste and individual style. Theories of aesthetic taste are valuable for psychological, cultural, anthropological, social and other research, but their practical significance is equally important. Attention to aesthetic taste can help to make better decisions, create fairer policies, and develop higher-quality products. The article substantiates the idea that aesthetic intelligence entails an analytical advantage in constructing experience. In epistemology, aesthetic intelligence is researched as a horizon of new ideas through productive imagination and a form of organizing experience (I. Kant, P. Ebbs). The article has also attempted to demonstrate the essential features of this phenomenon, such as the “ability to perceive and interpret beauty” (P. Ferrucci, P. Brown). Considering that aesthetic intelligence is a form of artistic (creative) world perception and a tool for constructing experience, which goes beyond perception and narrow instrumental rationality, these definitions can be revised and significantly expanded. Aesthetic intelligence can be interpreted not only as the “ability to perceive and interpret beauty” but also as constructive thinking aimed at appropriateness, novelty, and uniqueness, as well as creativity and its organized results.